Brown Recluse Spider, Loxosceles reclusa Gertsch and Mulaik (Arachnida: Araneae: Sicariidae) - Glavis B. Edwards, Jr. (EDIS)
The brown recluse spider, Loxosceles reclusa Gertsch & Mulaik, is frequently reported in Florida as a cause of necrotic lesions in humans. For example, in the year 2000 alone, Loft (2001) reported that the Florida Poison Control Network had recorded nearly 300 alleged cases of brown recluse bites in the state; a subset of 95 of these bites was reported in the 21 counties (essentially Central Florida) under the jurisdiction of the regional poison control center in Tampa. This document is EENY-299 (originally published as DPI Entomology Circular 406), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2003.